Media, family and colourism: a sociological exploration of body shaming among young women in rural Tamil Nadu - Kumaran, Rajagopal (Journal of Social Review and Development, 2024)
Body shaming refers to the act of disparaging or ridiculing a person's physical appearance. This research paper examines the lived experiences of young women in Tamil Nadu who have faced body shaming, employing a phenomenological approach to elucidate how societal expectations and cultural norms influence their self-perceptions and body image. The study demonstrates the widespread occurrence of body shaming and its considerable adverse effects on the participants' mental and emotional health. The results emphasize the influence of culture and social norms on individuals' body perceptions and the coping mechanisms they employ in response to body shaming. The study concludes by highlighting the necessity of addressing the fundamental causes of body shaming and advocating for body positivity and acceptance.